Therapeutic Properties of Datura Stramonium (D. Stramonium) and its Medico Legal Aspect - Bhushan, Bharat; Singh, Jaram; Sason, Rajveer; Kaur, Kulwinder (International Research Journal of Ayurveda & Yoga, 2022)
Various diseases can be treated and managed with plants, and they have been utilized in many nations to cure a variety of disease situations. Plants have therapeutic potential because of their bioactive phytochemical components, which have specific physiological effects on living things. Many therapeutic plants include chemical components that, when ingested in large doses, may have adverse effects on individuals. Despite having medical properties, plants with high concentrations of alkaloids could become poisonous. One of the well-known folk medicines with widespread use is Datura, a member of the Solanaceae family, also known as Jimson weed and as "Jaozmasel" in Arabic. Chemical analysis of this plant revealed its components as alkaloids, carbohydrates, and proteins, among which alkaloids including scopolamine, hyoscyamine, and atropine are the main active ingredients that exhibit various activities, such as anti-asthmatic. In addition to being used medicinally, Datura is one of the most abused plants in the world due to its widespread availability, particularly in Africa, Southeast Asia, and India, where it is primarily used for spiritual or religious purposes and has a much higher rate of negative reports than other psychoactive substances. When used excessively or abused, it can have poisonous side effects including delirium, mydriasis, mental disorientation, psychosis, and even violent conduct. In this review, various decorative appeal of the medicinal value of Datura has been mentioned along with its medico legal importance.